Evaluating the Risks in Acquisition - HERTZ, David B. (Institutional Knowledge at Singapore Management University, 1982)
This paper aims to illustrate the role of strategic risk analysis in the process of policy dialogue. An example of a new product diversification demonstrates the role of risk analysis in clarifying problem assumptions and in understanding the impact of uncertainty on decision-making. Risk analysis is seen as an adjunct and aid to problem formulation and resolution and not an end in itself.